Driving Pressure and Normalized Energy Transmission Calculations in Mechanically Ventilated Children Without Lung Disease and Pediatric Acute Respiratory Distress Syndrome*. Issue 10 (1st June 2021) - Díaz, Franco; González-Dambrauskas, Sebastián; Cristiani, Federico; Casanova, Daniel R.; Cruces, Pablo
Abstract : OBJECTIVES: To compare the new tools to evaluate the energy dissipated to the lung parenchyma in mechanically ventilated children with and without lung injury. We compared their discrimination capability between both groups when indexed by ideal body weight and driving pressure. DESIGN: Post hoc analysis of individual patient data from two previously published studies describing pulmonary mechanics. SETTING: Two academic hospitals in Latin-America. PATIENTS: Mechanically ventilated patients younger than 15 years old were included. We analyzed two groups, 30 children under general anesthesia (ANESTH group) and 38 children with pediatric acute respiratory distress syndrome. INTERVENTIONS: Respiratory mechanics were measured after intubation in all patients. MEASUREMENTS AND MAIN RESULTS: Mechanical power and derived variables of the equation of motion (dynamic power, driving power, and mechanical energy) were computed and then indexed by ideal body weight. Driving pressure was higher in pediatric acute respiratory distress syndrome group compared with ANESTH group. Receiver operator curve analysis showed that driving pressure had the best discrimination capability compared with all derived variables of the equation of motion indexed by ideal body weight. The same results were observed when the subgroup of patients weighs less than 15 kg. There was no difference in unindexed mechanical power between groups. CONCLUSIONS: Driving pressure is the variable that better discriminates pediatric acute respiratory distress syndrome from nonpediatric acute respiratory distress syndrome in children than the calculations derived from the equation of motion, even when indexed by ideal body weight. Unindexed mechanical power was useless to differentiate against both groups. Future studies should determine the threshold for variables of the energy dissipated by the lungs and their association with clinical outcomes.